CDM 2015 questions and answers : a practical approach to design, safety and wellbeing - Perry, Pat, 1954- (ICE Publishing, 2021)
This is a practical handbook which provides best practice solutions to a comprehensive set of frequently asked questions about the CDM Regulations, explaining the 2015 updates clearly and logically in order to ensure that readers can implement them as quickly and as smoothly as possible.